2016
DOI: 10.1161/circinterventions.115.003635
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New-Onset Left Bundle Branch Block and Periprocedural Permanent Pacemaker Implantation on Clinical Outcomes in Patients Undergoing Transcatheter Aortic Valve Replacement

Abstract: Background-Available data on the clinical impact of new-onset left bundle branch block (LBBB) and permanent pacemaker implantation (PPI) after transcatheter aortic valve replacement (TAVR) remains controversial. We aimed to evaluate the impact of (1) periprocedural new-onset LBBB or PPI post-TAVR on cardiac mortality and all-cause 1-year mortality and (2) new-onset LBBB on the need for PPI at 1-year follow-up. Methods and Results-We performed a systematic search from PubMed and EMBASE databases for studies rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
147
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(164 citation statements)
references
References 43 publications
9
147
2
6
Order By: Relevance
“…Postprocedurally, the occurrence of pLBBB was associated with higher rates of permanent pacemaker implantation, which is also reported in other trials . The major indications for pacemaker implantation were third‐degree atrioventricular block in 76.0% of all patients, as described by others . In contrast to this, in a subanalysis of the PARTNER trial Nazif et al identified in only 46.7% high‐degree atrioventricular block as indication for pacemaker implantation with use of balloon‐expandable valves.…”
Section: Discussionsupporting
confidence: 60%
“…Postprocedurally, the occurrence of pLBBB was associated with higher rates of permanent pacemaker implantation, which is also reported in other trials . The major indications for pacemaker implantation were third‐degree atrioventricular block in 76.0% of all patients, as described by others . In contrast to this, in a subanalysis of the PARTNER trial Nazif et al identified in only 46.7% high‐degree atrioventricular block as indication for pacemaker implantation with use of balloon‐expandable valves.…”
Section: Discussionsupporting
confidence: 60%
“…This is an important finding as NOP-LBBB can associate with lack of improvement in left ventricular ejection fraction, poorer functional status, and may also increase the risk of sudden death, especially in those patients with larger QRS. [18][19][20][21] Furthermore, a recent systematic review and meta-analysis including 17 studies showed that new-onset LBBB post TAVR is a marker of an increased risk of cardiac death and the need for permanent pacemaker implantation at 1-year follow-up. 21 Of note, in a previous analysis of the Brazilian registry, with fewer patients and mostly with the CoreValve bioprosthesis, BAVP was associated with an increased need for permanent pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Furthermore, a recent systematic review and meta-analysis including 17 studies showed that new-onset LBBB post TAVR is a marker of an increased risk of cardiac death and the need for permanent pacemaker implantation at 1-year follow-up. 21 Of note, in a previous analysis of the Brazilian registry, with fewer patients and mostly with the CoreValve bioprosthesis, BAVP was associated with an increased need for permanent pacemaker implantation. 15 This finding, which was not replicated in our expanded series, make us think that pacemaker implantation after TAVR may be influenced by multiple factors, including liberality of indication, previous conduction disturbances, and technical factors such depth of implantation of the THV and also BAVP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis of patients post TAVR with LBBB or PPI demonstrated a trend toward an increase in mortality with LBBB with a relative risk of 1.39, with early PPI negating this risk. 33 Periprocedural PPI itself was not associated with an increase in mortality. Post-TAVR LBBB and pacing-induced dyssynchrony may be reasons for worsened outcomes in this population.…”
Section: Discussionmentioning
confidence: 94%